Energy transmission processes in the effectuation chain of solar forcing to the terrestrial atmosphere—a review - Wang, Jingsong; Zhao, Liang; Xiao, Ziniu; Zhang, Peng; Ren, Zhipeng; Zong, Weiguo; Qi, Jin; Huang, Cong; Xu, Ying; Lu, Yixiong (Frontiers in Earth Science, 2023)
The Sun has an obvious quasi-11-year cycle and numerous short-term eruptive activities. There are four processes of energy transmission in the effectuation chain of solar forcing to the climate system: solar energy input into the atmosphere, atmospheric absorption of the input energy, transformation of the absorbed energy into dynamic and thermodynamic responses in the atmosphere, and coupling among all the layers affected by solar forcings. However, the four processes have not been discussed in their entirety. This present paper reviews studies over the last decade on how solar radiation varies during the solar cycle and solar eruptions, and, correspondingly, how the terrestrial atmosphere absorbs the input solar energy.